Decolonialization of Contemporary Science According to Professor Syed M. Naquib al-Attas as the Aufklarung Movement in Islam - Asr Himsyah, Unun Zumairoh; Hasib, Kholili (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2023)
Through education, science is expected to be able to provide good and significant changes to human life. In realizing this, Muslim scholars are trying to develop established scientific theories in various fields based on the Islamic worldview. However, in the era of modernization and post-modernization, the Islamic scientific tradition is slowly losing the fundamental aspects of science, worldview and empistemology. In practice, epistemology is separate from theology, this separation is the impact of the secularization of science. Syed Naquib al-Attas is one of the contemporary Muslim scholars who initiated the Islamization of science as a response to the secularization of science, where he returned science to the Islamic scientific tradition. By using library research methods, furthermore, it is hoped that this research can elaborate on the concept of Islamization of science as an era of enlightenment (Aufklarung) developed by al-Attas became the basis of Islamic knowledge. This research finds that decolonialization of secular science is an important step in elaborating al-Attas towards the Islamization of contemporary science.